RECONHEMENTO FOTOGRÁFICO:: ANÁLISE DO HC598886/SC NOS ACÓRDÃOS DO TRIBUNAL DE JUSTIÇA DO PARANÁ ENTRE JANEIRO DE 2022 A JULHO DE 2022 - Rodrigues de Almeida, Fernando (2023)
Photographic recognition plays a crucial role in the identification and conviction of suspects in Criminal Proceedings. Widely accepted as a means of evidence, this tool involves the presentation of photographs of individuals, objects, or scenes related to a crime, allowing witnesses or victims to identify the suspect or provide relevant information to the case. Recently, the 6th Chamber of the Supreme Court of Justice ruled in favor of a Writ of Habeas Corpus, establishing the mandatory nature of the procedural formalities outlined in Article 226 of the Code of Criminal Procedure for the use of photographic recognition. Failure to comply with the prescribed procedure renders the evidence invalid. Therefore, the use of photographic recognition must be approached with caution and in accordance with legal principles to avoid identification errors and ensure justice within the criminal justice system. This article aims to analyze the use of photographic recognition as evidentiary means in appeals filed in the Paraná State Court of Justice during the period from January to July 2022. The study employs a methodological approach that combines the hypothetical-deductive method with a qualitative-descriptive method to establish the legal and procedural foundations of photographic recognition and investigate the decisions related to these methods in the aforementioned court. Initially, the article presents a comprehensive literature review exploring the theoretical basis of photographic recognition as a means of evidence in the legal context. Subsequently, the research focuses on a qualitative-descriptive analysis of the decisions made by the Paraná State Court of Justice during the study period. In line with the aforementioned, the article presents the results that provide a comprehensive overview of the use of photographic recognition as evidentiary means in the appeals of the Paraná State Court of Justice.